THE STATE AND PROSPECTS FOR VITAL ACTIVITIES IN THE RADIOCONTAMINATED AREAS OF ZHYTOMYR POLISSYA - Malynovsky, Anton (Acta Scientiarum Polonorum. Oeconomia, 2006)
The paper deals with the after-effects of the radioactive contamination of Zhytomyr province. In 1986, Ukrainian government decided to divide the area into 4 zones: the restricted access zone, the zone of obligatory resettlement, the zone of the guaranteed voluntary resettlement and the zone of the strict radiological control. The paper also analyses the ecological and socio-economic situation in the region 20 years after the Tchernobyl disaster. Not all citizens agreed to be displaced and many of them come back. Nowadays, about 4.5 thousand people live in the province. The long-term trends in the development of the economy and improvement of vital activities conditions in Zhytomyr Polissya have been determined.